Comparison of The Mechanical Properties of Low-Cost Bio Fiber Reinforced Polymer Composites - Sanad Abdulkareem Ismael; Samara Munaem Naeem (International Journal of Applied Mechanics and Engineering)
In this study, the physical, and mechanical properties of low-cost and biocomposites were evaluated. The walnut shell and date palm frond fibers were thermally treated in an oven at a temperature of 70°C and then chemically treated with NaOH and distilled water solution, after these treatments, the biocomposite materials will be thermally treated again at 50°C. This procedure was performed for three types of biocomposite; Walnut shell Fiber Reinforced Polymer (WFRP), Date palm Fiber Reinforced Polymer (DFRP), and Hybrid Fiber Reinforced Polymer (HFRP), whereas the biocomposite sheets consisting of 30% biofibers and 70% unsaturated polyester, the mechanical test specimens were cut by a CNC machine according to ASTM standards. The effect of fiber type was analyzed in terms of the mechanical properties (tensile, compression, and density). The tensile test results showed that the DFRP composite had the best results comparable with WFRP and HFRP, the ultimate tensile strength, was increased by 28.6%, and 12.5% respectively, furthermore, the compression strength of the WFRP composite was increased by 21.5%, and 10.3% compared with DFRP and HFRP composites respectively. The WFRP composite revealed the lowest value of density 4.60 g/cm3 rather than DFRP and HFRP composites.